Contemporary Factors Associated with the Use of Laparoscopy for Inguinal Hernia Repair Among Department of Defense Beneficiaries. Issue 9 (4th April 2018) - Madenci, Arin L; Wolf, Lindsey L; Jiang, Wei; Koehlmoos, Tracey P; Learn, Peter A; Haider, Adil H; Smink, Douglas S
Abstract: Introduction: The factors that contribute to variation in utilization of laparoscopic inguinal hernia repair are unknown. We sought to determine the current usage patterns of laparoscopic and open surgery in the elective repair of uncomplicated unilateral inguinal hernia in a large population with universal health care coverage comprised of Department of Defense (DoD) beneficiaries. Materials and methods: The DoD Military Health System Data Repository (MDR) tracks health care delivered to a universally insured population of active/reserve/retired members of the U.S. Armed Services and their dependents. The MDR was queried for elective unilateral inguinal hernia repair among adult patients between 2008 and 2014. The primary outcome was laparoscopic (vs. open) approach to hernia repair. We conducted univariable and multivariable analyses of patient- and systems-level factors associated with approach to inguinal hernia repair. This research was approved by our institutional review board prior to commencement of the study and need for informed consent was waived given the design of this study. Results: Among 37, 742 elective uncomplicated unilateral inguinal hernia repairs, 35% ( n = 13, 114) were performed laparoscopically. In 2014, 40% of inguinal hernia repairs were performed laparoscopically, compared with 27% of repairs in 2008 ( P < 0.01). In multivariable analysis, laparoscopic hernia repair was more likely for male patients (OR = 1.38, 95% CI = 1.23–1.54, P < 0.01), military (vs. civilian) institutions (OR = 1.34, 95% CI = 1.28–1.41, P < 0.01), active-duty officers (vs. active-duty enlisted; OR = 1.21, 95% CI = 1.12–1.30, P < 0.01), and more recent year of surgery ( P < 0.01). Laparoscopic repair was significantly less likely among patients with greater than one comorbidity (vs. none; OR = 0.68, 95% CI = 0.61–0.76, P < 0.01). Conclusion: In a large, universally insured population of military service members and their dependents, laparoscopic inguinal repair is increasingly used and was preferred over open repair for younger, healthier, active-duty patients and those treated within the military (vs. non-military) care system.